The influence of personal brand communication on consumers - Kromalcas, Saulius; Kraujalienė, Lidija; Ževžikovas, Gustas (Business: Theory and Practice, 2024)
The idea of this research is to combine the influence of personal brand with business needs. This article is a personal brand’s analysis on how personal brand influences consumer interest in products/services. An experiment is carried out on the content viewed by consumers using eye-tracking technology “Neuromarketing & AI LAB” to reveal emotional and structural sensations in the social network Instagram. The aim of this research is to determine the influence of a personal brand on the consumer. Research methodology: analysis of scientific literature, logical definition and theory construction, an experiment: research of human emotions and chosen content. Data analysis method: descriptive statistics and comparative analysis. AOI (heat map) was selected to illustrate the research results. Influencers with up to 100 000 followers were selected – stimuli that trigger or enhance physiological and psychological reactions in the body. It was found that the body and face of a personal brand had the higher influence on consumers. Personal brand attracts consumers’ attention and promotes engagement. The originality and value of the paper: content relevance research of personal brand (identity) influence on consumers in social network Instagram. Further we suggest carrying out similar personal brand’s research choosing other social networks.